Use of robotics education as a tool in the process of teaching (2010)
Through educational robotics, concerning the use of didactic and pedagogic can support teaching and learning processes in the educational community with technological tools. This document describes the implementation of a differential mobile robot configuration built with the set pieces of kit Lego MindtormsTM NXT robotics, to support teaching and learning processes in three elementary schools from the State of Boyacá, in Colombia. Moreover, the state of art of similar applications is established and the guidelines for building the robot and the results of its application in the educational environment are presented. In addition, it is generally clear, the potential for learning environments, developed from the educational robotics as a new teaching proposal that meets the requirements of contemporary societies that demand new teaching methods.